2018
DOI: 10.15294/jbat.v6i2.12507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solid Vinasse-Based Organic Fertilizer on Some Growth Indices of Tomato Plant

Abstract: Vinasse, which is commonly referred to as stillage, is a aqueous by-product of bioethanol processing. This side-product is yielded in a very large quantity in bioethanol industry since the production of 1 L of ethanol will generate 13 L of vinasse. Hence it is become a problem of bioethanol industry since vinasse waste doesn't have economic value and harmful to the environment. This industrial waste has high COD and BOD, high acidity, and high temperature when discharged from the bottom of distillation unit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The acidity (pH) of vinasse was adjusted by the addition of 40% NaOH solution until it reached pH 7 (neutral). Subsequently, vinasse was evaporated at the temperature of 100 C for 1 h to remove the water and volatile compounds content until the volume of vinasse reached 80 mL (Kusumaningtyas et al 2017). After being cooled, vinasse was then mixed with the other feedstocks as depicted in Table 10.3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acidity (pH) of vinasse was adjusted by the addition of 40% NaOH solution until it reached pH 7 (neutral). Subsequently, vinasse was evaporated at the temperature of 100 C for 1 h to remove the water and volatile compounds content until the volume of vinasse reached 80 mL (Kusumaningtyas et al 2017). After being cooled, vinasse was then mixed with the other feedstocks as depicted in Table 10.3.…”
Section: Methodsmentioning
confidence: 99%
“…Vinasse has macro-and micronutrients including N, P, K, Ca, Mg, Fe, Mn, Zn, and Cu which are useful and required for plant to grow (Madubaru 2008). Vinasse has been used as solid organo-mineral fertilizer (Kusumaningtyas et al 2017). Vinasse can also be processed into liquid organic fertilizer through fermentation and non-fermentation process.…”
Section: Vinassementioning
confidence: 99%
See 1 more Smart Citation
“…Several scientific groups (Dirbeba et al, 2019a;2019b;Gurgel et al, 2015;Kamalia et al, 2021;Kusumaningtyas et al, 2015;2020) have studied the process of solid OMF vinasse base. While others (Anas et al, 2007;Kusumaningtyas et al, 2017) have reported the positive impact of OMF vinasse based on the productivity of tomatoes (Solanum lycopersicum L.) and sugarcane.…”
Section: Case Example In Elaboration Of Peat-free Soil Amendmentmentioning
confidence: 95%
“…Vinasse is one of the liquid wastes produced from the bioethanol industry with the amount generated is 9-14 L/L ethanol (Kose et al, 2018). Vinasse is a potential raw material for the fertilizer due to its nutrient content such as nitrogen, phosphorus, and potassium, which can support agriculture crops growth (da Silva Paredes et al, 2014) (Kusumaningtyas et al, 2017). The utilization of vinasse as a fertilizer is gaining interest in the sugarcane biorefinery (da Silva Paredes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%